For the -b formula, let us say that your sum is 2x^2 ( two x squared ) + 3x - 4
So 2^2 will be a
3 will be b
And -4 will be c
We don't write down 3x because that will make the answer wrong
So then your formula is -b±√b^2(b squared)-4ac ÷ 2a
So then we substitute
-3±√3^2-4(2)(-4)÷2(2)
-3±√9+32÷4
The ± means that it will be either + or -
So -3+√9+32÷4= -1.4 (rounded)
Or -3-√9+32÷4= -4.6 (rounded )
So then
x = 1.4
Or
x = 4.6
Hope this helps ^°^

You use this formula only if it says in the question, round to two (or three) decimal places. When it does not say this, you factorise instead.
X(squared) - 8x + 16 = 0
First open up two brackets
( )( ) = 0
Then add the x squared
(X )(X ) = 0
Then look at the sign in front of the last number (16 in this case). It's a + so, the signs in the brackets will be the same. Then you look at the middle number (8 in this case) and then look at the sign. Since the signs will be the same, you put down two minus' in the brackets. And then find factors of 16 and substitute two factors into the brackets that equal to minus 8.
(X - 4) (X - 4) = 0
-4X
-4X
= -8X
^ so this is the correct factors you have chosen
Then you let each bracket equal 0
X - 4 = 0
X = 4
X - 4 = 0
X = 4
Your answer is
X = 4

Marklogan— 14/05/16